The little book of website quality control - Meiert, Jens Oliver (O'Reilly Media, 2017)
Why bother with quality control when building a website? Simple. Quality control (QC) helps you determine whether your site meets your own expectations and, more important, whether it meets professional best practices. Without QC, you have no way of telling whether your site is any good prior to unleashing it upon the world. QC can save you time, money, and a lot of anxiety. This short book covers QC for several website aspects--such as security, functionality, and code quality--and provides links to many useful tools that can help you in each of these areas. Author Jens Oliver Meiert also explores important areas of QC in practice, which requires training and is dependent on team mindset, automation, and enforcement. Due to key differences in approach, this ebook focuses specifically on quality control for websites rather than web apps. This ebook covers: Security Accessibility Usability Performance Functionality Maintainability Semantics Validation Design consistency and layout Typography Code quality Coding standard compliance.